The effect of structured versus unstructured collaborative pre-writing task on writing skills of the Iranian EFL students - Maryam Beiki; Neda Gharagozloo; Reza Raissi (Asian-Pacific Journal of Second and Foreign Language Education, 2020)
Abstract Writing is considered a very complicated task for many EFL students and Iranian EFL learners have many problems in this regard. Present study through a mixed method design, attempted to investigate the effect of Structured Collaborative (SC) pre-writing task versus Unstructured Collaborative (USC) pre-writing task on the writing ability of Iranian EFL students. Among a population of 300 freshmen learners of English language translation of Islamic Azad University, 169 students were selected based on criterion sampling. The criteria for selecting the sample were English language proficiency of the learners, age of the participants and major of their study. On the other hand, 30 teachers were selected based on convenience sampling for the interview part of the study. Then the students were assigned to Unstructured Collaborative (USC), and Structured Collaborative (SC) pre-writing groups. These two clusters were considered as experimental group and as control group. The study was implemented over a period of 16 weeks and involved pre and post-tests. Results of the quantitative data analysis shows that students’ writing proficiency in both groups were improved. However, the outcomes of the study reveals that the (USC) group outperformed the (SC) group. The qualitative data analysis through classroom observation and teachers interview reveals that teachers of (IAU) practiced the collaborative tasks at the three stages of writing in their classes and they also favored and applied the five components of Cooperative Learning (CL). In this study, the researchers took the initiative to make a distinction between structured and unstructured collaborative pre-writing tasks. Consequently, the results of the current study are of benefit for several groups of people, namely language practitioners, university students and educational administrators.